Amnesty and (in)justice in Brazil: the duty of justice and impunity - Silva, Márcio Seligmann (2007)
The article deals with the aporias implied in the memory of the Brazilian civil-military dictatorship of 1964-1985. It analyzes the difference between the initial concept implicit in the claims for amnesty on the part of the opposition and, on the other hand, the 1979 amnesty, imposed by the agents of the dictatorship. This amnesty has implied, until today, impunity for crimes committed by state terrorism. The text presents the existing need in the work of memory after exceptional regimes to bring the truth to light as well as to carry out a "duty of justice". Only through this process can society try to build democracy and the rule of law. The obliteration of memory and the impediment of the work of justice lead society to remain trapped in its past and to repeat the same violent structure. The text also analyzes the verses of the song "Angélica" by Chico Buarque as a way of working with the traumatic memory of the dictatorship.